1997
DOI: 10.1111/j.1744-9987.1997.tb00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytapheresis with Leukocyte Removal Filter as New Therapy for Ulcerative Colitis

Abstract: Leukocytapheresis (LCAP) with a leukocyte removal filter column was administered for 45 patients with ulcerative colitis (UC). We evaluated changes in the leukocyte count and the differential percentages during LCAP. Cytokine production was assessed from each patient's peripheral mononuclear cells or monocytes. Flow cytometry was performed to assess the removal rates of activated cells and adhesion molecule positive cells by LCAP. Clinical improvement was recognized in 35 of 45 patients during intensive LCAP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 4 publications
4
105
1
2
Order By: Relevance
“…This is similar to the previous studies in patients with rheumatoid arthritis and ulcerative colitis and healthy volunteers (23)(24)(25). It has been reported that the peripheral blood platelets were removed while passing through the column (26).…”
Section: Discussionsupporting
confidence: 79%
“…This is similar to the previous studies in patients with rheumatoid arthritis and ulcerative colitis and healthy volunteers (23)(24)(25). It has been reported that the peripheral blood platelets were removed while passing through the column (26).…”
Section: Discussionsupporting
confidence: 79%
“…During LCAP, most of the leukocytes are removed by a filter during extracorporeal circulation. This treatment is associated with rebound leukophilia in response to transient leukopenia (49,50), indicating a rapid cell release response from the reticuloendothelial system. Therefore, this drastic change in gene expression may be partly explained by the replacement of activated leukocytes with new and naĂŻve ones originating from the marginated pool and/or bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…As no previous study had been performed in Japan on the use ofLCAP for Crohn's disease, it was necessary to conduct this in the form of a preliminary study, rather than in the more desirable form of a controlled study. The filters adopted for this study were leukocyte removal filters known to remove nearly 100% of granulocytes and monocytes, 70 to 80% of lymphocytes, and 30 to 40% of platelets, but little or no red blood cells (17,18). The protocol required long periods for both the intensive and the maintenance therapy, in view of the long term of treatment which is generally required for the control of Crohn's disease by drug therapy.…”
Section: Introductionmentioning
confidence: 99%